DESAIN ARSITEKTUR KNOWLEDGE MANAGEMENT SYSTEM LAYANAN JASA KALIBRASI DI UPT BPI LIPI DENGAN MENGGUNAKAN SOFT SYSTEM METHODOLOGY - Fakhrurroja, Hanif (Teknologi Indonesia, 2010)
The age range of UPT BPI LIPI employees is relatively unbalanced. 71,42% of the employees have already exceeded 40 years old and 58,73% of them will be retired in 2015. Based on these facts, UPT BPI LIPI needs a Knowledge Management System (KMS) that can store knowledge assets of the employees. Soft Systems Methodology (SSM) is used as a method to identify the knowledge and to develop the best architecture design of KMS for UPT BPI LIPI. There are fi ve stages in the knowledge management cycle for calibration services in UPT BPI LIPI, namely knowledge acquisition, knowledge extraction, knowledge storage, knowledge sharing, and knowledge update. The result of SSM showed that KMS design can be applied to create knowledge, to share knowledge, to record knowledge, to store knowledge, and to reuse knowledge, so it can be optimize the calibration services in UPT BPI LIPI.